2018
DOI: 10.3390/en11113093
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Wood-Based Panels Integrated with a Bio-Based Phase Change Material: A Full-Scale Experiment in a Cold Climate with Timber-Frame Huts

Abstract: The relatively low thermal mass of timber frame buildings is a limiting factor for their energy efficiency and for the thermal comfort. The aim of this study is to assess the performance of wood-based wallboards integrated with PCM (Phase Change Materials) in a cold climate (Québec, Canada), from the heating season to the summer. Two timber-frame test huts, of 2 × 2.5 × 3 m, were built following the National Building Code of Canada and placed in the LAVAL University Campus. The first hut was equipped with wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“… 7 Paraffins and fatty acids have been proposed in buildings, for example, for use in the construction walls or in storage units, to harvest solar energy and moderate the energy consumption. 8 10 Thus, incorporation of PCMs in buildings improves their energy efficiency and maximizes renewable energy in the construction sector, which is responsible for a large share of the global energy demand. Various other segments of industry, such as active-packaging, refrigeration, electronics, sensors, and those associated with waste heat recovery can benefit from these versatile materials.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Paraffins and fatty acids have been proposed in buildings, for example, for use in the construction walls or in storage units, to harvest solar energy and moderate the energy consumption. 8 10 Thus, incorporation of PCMs in buildings improves their energy efficiency and maximizes renewable energy in the construction sector, which is responsible for a large share of the global energy demand. Various other segments of industry, such as active-packaging, refrigeration, electronics, sensors, and those associated with waste heat recovery can benefit from these versatile materials.…”
Section: Introductionmentioning
confidence: 99%
“…The timber frame buildings low thermal mass can be considered as a negative factor to their thermal comfort and their energy efficiency. In Quebec City (Canada) with its cold weather, Mathis et al 84 experimented on two wood‐based timber frame test huts of 2 m × 2.5 m × 3 m, as shown in Figure 26 as one of them integrate a bio‐based PCM. The PCM panels effectiveness evaluation and comparative analysis between the two cabins were carried out over several seasons.…”
Section: Application Of Pcm In the Thermal Management Of Buildingsmentioning
confidence: 99%
“…This panel consists of three layers including an MDF and a high-density fiberboard (HDF) panel, as well as a plastic bag of PCM ( Figure 1) [54]. few studies on the application of PCM in wood-based panels [50][51][52][53][54]; however, the environmental performance of PCM in wood-based panels is yet to be evaluated. LCA and SLCA methods can be viewed as parallel subjects and the use of SLCA does not prevent LCA practitioners from applying a full LCA.…”
Section: Pcm Panelmentioning
confidence: 99%
“…They indicated that the environmental impact of PCM-incorporated ventilated double skin facades (VDSF) was three times that of the alveolar bricks. There are few studies on the application of PCM in wood-based panels [50][51][52][53][54]; however, the environmental performance of PCM in wood-based panels is yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%